COWORKING SPACE DI KOTA PONTIANAK DENGAN PENDEKATAN PRINSIP FLEKSIBILITAS DALAM ARSITEKTUR - Nurhidayati Nurhidayati; Valentinus Pebriano; Syaiful Muazir (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2023)
The freelancer profession in the current era is in great demand by many people. In the world of freelancing, income and place of work are not fixed. Most freelancers have little business capital in leveraging skills and building relationships. In addition, freelancers do not have a limit on working time, but are free to determine where to work. Freelancer activity facilities in Pontianak City do not support convenience. They are active in cafes or coffee shops with a low level of privacy. Freelancers and other creative industry players need a place that is comfortable for their activities, both working, socializing, and collaborating in running their business. They need a container that fits their activities, namely coworking space. Coworking space is a multifunctional workplace that combines various commercial functions, such as offices, meetings, culinary, entertainment, and others. For this reason, it is necessary to design a coworking space in Pontianak City. The purpose of a coworking space is to accommodate various work activities, both individually and in groups, along with their supporting activities. The design method used is flexibility in architecture, including adaptable and universal space. The steps used are looking for problems, identifying, collecting data, analyzing, conveying ideas, selecting ideas, designing products, and evaluating. The expected result is a flexible spatial plan inside and outside the coworking space, adapting to the dynamics of freelancers and other users.